Motor unit loss and weakness in association with diabetic neuropathy in humans. Issue 2 (30th April 2013) - Allen, Matti D.; Choi, In Ho; Kimpinski, Kurt; Doherty, Timothy J.; Rice, Charles L.
ABSTRACT Introduction Diabetes mellitus can be associated with peripheral neuropathy which may affect numbers of functioning motor units (MUs) of limb muscles. Direct quantitative assessment of MU numbers and muscle strength have not been performed in humans. We compared the estimated number of MUs of individuals with diabetic polyneuropathy (DPN) versus controls. Methods Patients with signs/symptoms of DPN were studied using decomposition‐enhanced quantitative electromyography of the tibialis anterior (TA). Motor unit number estimates were derived from this analysis. Results Dorsiflexion strength was ∼60% less in DPN than controls (P < 0.05). Additionally, the estimated number of functioning TA MUs was ∼60% fewer in patients with DM (∼46) versus controls (∼111) (P < 0.05). Conclusions These data directly measure MU loss associated with DPN in a proximal muscle in humans. It remains to be determined whether quantifying MU loss has clinical utility in monitoring the progression or management of DPN. Muscle Nerve, 48: 298–300, 2013